2015
DOI: 10.3390/ijms16036464
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Chromosome Ideogram Representation of Currently Recognized Genes for Autism Spectrum Disorders

Abstract: Recently, autism-related research has focused on the identification of various genes and disturbed pathways causing the genetically heterogeneous group of autism spectrum disorders (ASD). The list of autism-related genes has significantly increased due to better awareness with advances in genetic technology and expanding searchable genomic databases. We compiled a master list of known and clinically relevant autism spectrum disorder genes identified with supporting evidence from peer-reviewed medical literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 54 publications
0
66
0
2
Order By: Relevance
“…The original gene lists reported in the literature included 792 genes for ASD [21], 290 genes for bipolar disorder [22] and 560 genes for schizophrenia [23], and of these, 23 genes were found in common in all three conditions (see Table 1). Functional analysis of the 23 genes identified from the submitted list of genes showed a high match for schizophrenia (17 genes, score = 15.1) with medium-match scores representing 25 other disorders including bipolar disorder (nine genes, score = 9.6) and autism spectrum disorder (10 genes, score = 9.1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original gene lists reported in the literature included 792 genes for ASD [21], 290 genes for bipolar disorder [22] and 560 genes for schizophrenia [23], and of these, 23 genes were found in common in all three conditions (see Table 1). Functional analysis of the 23 genes identified from the submitted list of genes showed a high match for schizophrenia (17 genes, score = 15.1) with medium-match scores representing 25 other disorders including bipolar disorder (nine genes, score = 9.6) and autism spectrum disorder (10 genes, score = 9.1).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we use the GeneAnalytics [20] program pathway analysis to further profile and characterize the underlying molecular architecture of clinically and etiologically relevant genes common to ASD [21], bipolar disorder [22] and schizophrenia [23] and associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Iossifov et al [2012] reported a male with a missense mutation (c.1997 A>G) in the TOP3B gene who also had autism. Butler et al [2015] identified TOP3B as a clinically relevant gene in a review of genes involved with autism spectrum disorders. Tan et al [2011] reported a male with a deletion encompassing only a subset of the area deleted in our patient and including over half of the TOP3B gene; this patient had phenotypic similarities to our patient, including learning difficulties and delay in expressive language skills.…”
Section: Resultsmentioning
confidence: 99%
“…Multiplex families and twin studies have shown that ASDs have a heritability as high as 90% [143,150,151]. This has led to a large number of genomic studies searching for the molecular etiology of ASD, which together have proposed 695 candidate genes [152] among them PCDH8, PCDHGA1, PCDHB15 [150], PCDH9 [146,153], PCDH10 [153,154], PCDH15 [155] , PCDHB4 [156], and the PCDHA gene cluster [157]. …”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 99%